2011
DOI: 10.1186/1465-9921-12-118
|View full text |Cite
|
Sign up to set email alerts
|

Mucin granule-associated proteins in human bronchial epithelial cells: the airway goblet cell "granulome"

Abstract: BackgroundExcess mucus in the airways leads to obstruction in diseases such as chronic bronchitis, asthma, and cystic fibrosis. Mucins, the highly glycosolated protein components of mucus, are stored in membrane-bound granules housed in the cytoplasm of airway epithelial "goblet" cells until they are secreted into the airway lumen via an exocytotic process. Precise mechanism(s) of mucin secretion, including the specific proteins involved in the process, have yet to be elucidated. Previously, we have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…This finding implies that TMF is required for mucus granule fusion, after granule translocation from the trans-Golgi compartment. These findings are corroborated by previous, independent proteomic studies, which indicated that TMF is part of the mucus granule complex and even associates with the granule membrane (22,23). To confirm this association, we used florescence microscopy to show colocalization of TMF with the MUC2 mucin in human colonic goblet cells.…”
Section: Discussionsupporting
confidence: 83%
“…This finding implies that TMF is required for mucus granule fusion, after granule translocation from the trans-Golgi compartment. These findings are corroborated by previous, independent proteomic studies, which indicated that TMF is part of the mucus granule complex and even associates with the granule membrane (22,23). To confirm this association, we used florescence microscopy to show colocalization of TMF with the MUC2 mucin in human colonic goblet cells.…”
Section: Discussionsupporting
confidence: 83%
“…Immunostaining was specific for CLCA1 and MUC5AC since there was no staining above background in the absence of primary antibody (Supplemental Figure 3). These findings are consistent with coordinated packaging of CLCA1 and MUC5AC within mucous granules as described previously (24,25) and, based on the present findings, concerted synthesis and secretion of CLCA1 and MUC5AC to the apical cell surface in response to IL-13-stimulation as well.…”
Section: Clca1 Controls Mucin Gene Expressionsupporting
confidence: 79%
“…Thus it is anticipated that apocrine secretion could result in disruption of cell membranes and introduction of intracellular and membrane proteins into the ASL. In support of this possibility, a recent proteomic study demonstrated that membrane-bound granules secreted from airway epithelial goblet cells contain cytoskeletal and regulatory proteins as well as mucins, suggesting that such granules may be a source for some of the intracellular proteins detected in ASL (69). Additionally, several groups have reported the presence of exosomes, microvesicles implicated in host defense and cell communication, in human BAL and cell culture secretions (1,39).…”
Section: Discussionmentioning
confidence: 88%